Novel perspectives on the PHD-HIF oxygen sensing pathway in cardioprotection mediated by IPC and RIPC - Martin-Puig, Silvia; Tello, Daniel; Aragonés, Julián (Frontiers in Physiology, 2015)
Reperfusion of ischemic cardiac tissue is the standard treatment for improving clinical outcome following myocardial infarction but is inevitably associated with ischemia-reperfusion injury (IRI). Ischemic myocardial injury can be alleviated by exposing the heart to brief episodes of sublethal ischemia-reperfusion prior to the ischemic insult, a phenomenon that has been termed ischemic preconditioning (IPC). Similarly, remote IPC (RIPC) is defined as transient episodes of ischemia at a distant site before a subsequent prolonged injury of the target organ. In this setting, adaptive responses to hypoxia/ischemia in peripheral tissues include the release of soluble factors that have the potential to protect cardiomyocytes remotely. Oxygen fluctuation is a hallmark of insufficient tissue perfusion and ischemic episodes. Emerging evidence indicates that prolyl hydroxylase oxygen sensors (PHDs) and hypoxia-inducible transcription factors (HIFs) are critical regulators of IPC and RIPC. In this minireview, we discuss recent findings concerning the role of the PHD-HIF axis in IPC and RIPC-mediated cardioprotection and examine molecular pathways and cell types that might be involved. We also appraise the therapeutic value of targeting the PHD-HIF axis to enhance cardiac tolerance against IRI.